Insect ecology : an ecosystem approach - Schowalter, Timothy Duane, 1952- (London, UK : Academic Press, 2016)
Insect Ecology: An Ecosystem Approach, Fourth Edition, follows a hierarchical organization that begins with relatively easy-to-understand chapters on adaptive responses of insect populations to various environmental changes, disturbances, and anthropogenic activities, how insects find food and habitat resources, and how insects allocate available energy and nutrients. Chapters build on fundamental information to show how insect populations respond to changing environmental conditions, including spatial and temporal distribution of food and habitat. The next section integrates populations of interacting species within communities and how these interactions determine structure of communities over time and space. Other works in insect ecology stop there, essentially limiting presentation of insect ecology to evolutionary responses of insects to their environment, including the activities of other species. The unique aspect of this book is its four chapters on ecosystem structure and function, and how herbivores, pollinators, seed predators, and detritivores drive ecosystem dynamics and contribute to ecosystem stability.
Print version record.
Keywords: Insects -- Ecology; SCIENCE -- Life Sciences -- Zoology -- General; Insects -- Ecology; Electronic books